Moving images : effective teaching with film and television in management - Billsberry, Jon; Charlesworth, Julie A.; Leonard, Pauline, 1957- (Emerald Publishing Limited : Information Age Publishing, 2012)
This book will inspire academics, teachers and trainers to use film and television in their classrooms and to shows them how it might be done. It brings together respected international scholars who recount their experiences of how they have used moving images in their classrooms (defined widely to include distance-learning) with their explanations of why they chose this method of teaching and how they put their intentions into action.The book also illustrates how particular subjects might be taught using film and television as an inspiration to demonstrate the range of opportunities that these media offer. Finally, this book considers some of the practical issues in using film and television in the classroom such as copyright, technology, and the representation of reality and drama in films.This is a 'practical, how to' book that answers the questions of those people who have considered using film and television in their classroom but until now have shied away from doing so. The opportunity to see how others have used film effectively breaks down psychological barriers and makes it seem both realistic and worthwhile.